Programa Ensino Médio Inovador no Espírito Santo : perspectivas de mudança ou continuidade nas políticas do ensino médio - Nardoto, Cláudia de Souza (2015)
This study is part of the major project "Innovative High School Program: working conditions and teacher formation", coordinated by Professor Dr. Eliza Bartolozzi Ferreira, funded by CNPq (National Council for Scientific and Technological Development). The hypothesis that guides our investigation is that this program gets bureaucratized in the making process of the PRCs (Curriculum Restructuring Projects) because fixed at SIMEC (Integrated System of Monitoring and Implementation and Control of the Ministry of Education), it is realized much more as a mechanism for acquisition of financial resources. Even if this hypothesis orients our studies, we also understand that the whole process is transformed by a dialectical movement when various forces are held. In this case, the analysis of the PRCs can point a horizon of transformation and/or construction of an innovative practice within schools. In this disposal we have as main objective to analyze the implementation of ProEMI (Innovative High School Program) in the state educational system of Espírito Santo. Our specific objectives are: to study the ProEMI policy in Espírito Santo state; identify the criteria adopted by the state Department of Education (SEDU) for implementation of this policy and; analyze the Curriculum Restructuring Project (PRC) elaborated by the school units in the year 2013/2014 at the Metropolitan Region, in order to verify which are the high school improvement opportunities, as well as the clashes of the peculiarities of this education phase from this government policy. To achieve these goals we opted for an exploratory research, initially, that according to Triviños (1987), allows the researcher to increase his experience around a given problem, as well as familiarity with the subject (GIL, 2009). As well as documentary, because besides we access the legal documents available for analysis of the ProEMI, we have as a starting point the PRC developed by schools in order to apprehend the diverse nature of the implicit ideologies in each project. What, according to Michel (2009), enabled us from secondary data broaden the researcher's view of their object of study. Thus, we structured the dissertation into three chapters. In the first chapter we seek to present the researches on High School in Brazil, as well as the theoretical discussion about the structural duality of high school and the main policies that focused on this type of education. In the second chapter, we analyze the ProEMI as a curricular restructuring policy and its implementation in Espírito Santo state according to the Curriculum Guidelines for High School Education. At last, we present the organization of Curriculum Restructuring Projects designed by schools, from the data provided by SEDU, in order to glimpse the possibilities of an integrated school in a Gramsci concerning perspective.